The Identification of Arabic Teaching Models in Aliy Ma'had l Tahdid Anwau’ Ta’lim al-Lugah al-'Arabiyah fi al-Ma’had al-‘Aliy - Kaharuddin, Kaharuddin; Nawas, Kamaluddin Abu; Bahri, Ratni Bt. Hj.; Hussin, MD Noor Bin (Universitas Islam Negeri Raden Intan Lampung, 2022)
The study of teaching Arabic models in Aliy Ma’had was necessary to be conducted. It could make contribution in designing Arabic teaching. The purpose of this research was to analyze the models of Arabic teaching. This research was field research which the researcher obtained and collected data from the research location. Two types of data were used in this research namely primary data and secondary data. Primary data was obtained from sheikh of Ma'had, 3 chiefs of Ma'had, 10 teachers, and 30 students. Secondary data was obtained from alumni, documents, and online news that was related to the topic. In collecting data, observation, interview, documentation, and FGD were used. Miles and Huberman model was used in this research. The results showed that the teaching Arabic in Aliy Ma’had consisted of four models. First, teaching Arabic with a conventional model: teaching that took place in official classes. Second, teaching Arabic with an extracurricular model: teaching that takes place outside the classroom and is supported by conventional teaching to improve both Arabic language skills. Third, teaching Arabic with the halaqiyah model: students learnt classical Islamic sciences by sitting on the floor in front of the teacher, which took place in the mosque after every evening and dawn prayers. Fourth, teaching Arabic with visiting teacher’s house where students studied further to strengthen scientific and spiritual connections. This research suggested the teacher and the institution in improving this topic to contribute Arabic teaching development in Aliy Ma’had.